2023
DOI: 10.1055/a-2040-1651
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical View of Thoracodorsal Artery Variants Using Computed Tomography Angiography

Abstract: BACKGROUND The latissimus dorsi (LD) muscle has a dominant pedicle with one thoracodorsal artery and receives sufficient blood by segmental circulation through several perforators. Thus, it is widely used in various reconstructive surgeries. We are reporting on the patterns of the thoracodorsal artery analyzed by chest CT angiography. PATIENTS AND METHODS We analyzed the preoperative chest CT angiography results of 350 patients scheduled to undergo LD flap breast reconstruction following complete mastectomy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Some authors have used a computed tomography angiography 64-slice CT scanner (CTA-64) or 320-detector row computed tomography angiography (CTA-320) to investigate the “arterial tree” of flaps in the lower limbs, abdomen, or toe, obtaining clear images. 19 20 21 22 23 24 According to these researchers, the anatomical results obtained from MDCT and the surgical findings are remarkably consistent. 21 22 Given the limitations of the traditional dissection method and the clear advantages of the MDCT method in vessel studies, we sought anatomical studies and reports on the deltoid flap vascular pedicle that used CTA-320 for imaging.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Some authors have used a computed tomography angiography 64-slice CT scanner (CTA-64) or 320-detector row computed tomography angiography (CTA-320) to investigate the “arterial tree” of flaps in the lower limbs, abdomen, or toe, obtaining clear images. 19 20 21 22 23 24 According to these researchers, the anatomical results obtained from MDCT and the surgical findings are remarkably consistent. 21 22 Given the limitations of the traditional dissection method and the clear advantages of the MDCT method in vessel studies, we sought anatomical studies and reports on the deltoid flap vascular pedicle that used CTA-320 for imaging.…”
mentioning
confidence: 74%
“…In 2009, Sharma et al 18 described a variant case in which the axillary artery was divided into the brachial artery, the common trunk of the anterior and posterior circumflex branches, and the deep brachial artery. In 2023, Cho et al 19 reported variant cases of the origin of the PCHA. The PCHA originated from the distal part of the axillary artery following the classical description in 74% of cases, while it was observed from the subscapular artery in the remaining cases.…”
Section: Discussionmentioning
confidence: 99%
“…When the volume of the flap decreases and the size of the canal increases, there is an increased risk of aspiration and speech difficulties, which significantly impairs communication with the likelihood of problems arising. Therefore, in this study, we have proposed a design for tongue reconstruction using the LD flap, which is one of the flaps that can provide the largest volume in the human body and is easily accessible for reconstruction surgeons with fewer pedicle variants (18). The design is Figure 6.…”
Section: Discussionmentioning
confidence: 99%